Accuracy of intracranial electrode placement for stereoencephalography: A systematic review and meta‐analysis. (6th March 2017) - Vakharia, Vejay N.; Sparks, Rachel; O'Keeffe, Aidan G.; Rodionov, Roman; Miserocchi, Anna; McEvoy, Andrew; Ourselin, Sebastien; Duncan, John
Summary: Objective: Stereoencephalography (SEEG) is a procedure in which electrodes are inserted into the brain to help define the epileptogenic zone. This is performed prior to definitive epilepsy surgery in patients with drug‐resistant focal epilepsy when noninvasive data are inconclusive. The main risk of the procedure is hemorrhage, which occurs in 1–2% of patients. This may result from inaccurate electrode placement or a planned electrode damaging a blood vessel that was not detected on the preoperative vascular imaging. Proposed techniques include the use of a stereotactic frame, frameless image guidance systems, robotic guidance systems, and customized patient‐specific fixtures. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines, a structured search of the PubMed, Embase, and Cochrane databases identified studies that involve the following: (1) SEEG placement as part of the presurgical workup in patients with (2) drug‐resistant focal epilepsy for which (3) accuracy data have been provided. Results: Three hundred twenty‐six publications were retrieved, of which 293 were screened following removal of duplicate and non–English‐language studies. Following application of the inclusion and exclusion criteria, 15 studies were included in the qualitative and quantitative synthesis of the meta‐analysis. Accuracies for SEEG electrode implantations have been combined using a random‐effects analysis and stratified by technique. Significance: The published literature regarding accuracy of SEEG implantation techniques is limited. There are no prospective controlled clinical trials comparing different SEEG implantation techniques. Significant systematic heterogeneity exists between the identified studies, preventing any meaningful comparison between techniques. The recent introduction of robotic trajectory guidance systems has been suggested to provide a more accurate method of implantation, but supporting evidence is limited to class 3 only. It is important that new techniques are compared to the previous "gold‐standard" through well‐designed and methodologically sound studies before they are introduced into widespread clinical practice.